CONCEPTUAL APPROACHES TO THE CAREER STUDIES - Larisa V. Temnova; Filipp V. Malakhov; Evelina S. Voskanyan (Высшее образование в России)
This article examines sociological and economic approaches to the study of career. Connection between career and social mobility is explored. According to the economic approach, job promotion of an employee is analyzed in the context of the processes of production, distribution and consumption of limited resources. Stages of professional career are analyzed in the article The summarized results of sociological studies show that the term «career» is associated in the minds of Russians with social mobility and job promotion. One aspect of the study of career, namely graduates' employment, is analyzed. Various types and typical models of career development are examined. Special attention is given to the analysis of the careers of the graduates of sociological faculties of Russian universities. In the study it has been identified three types of career of a sociology graduate: a teacher (usually at university), a scientist and researcher, and a practicing sociologist. Using the developed theory the authors give their own definition of a career as a process of successive changes in official or professional (intra- and interinstitutional) status of an individual based on the development of professional competencies, taking into account his personal interests and needs of organization.